2020
DOI: 10.35706/eltinfc.v3i1.3698
|View full text |Cite
|
Sign up to set email alerts
|

English Needs Analysis for Economics Students: An Exploratory Research

Abstract: Learning specific English relevant to the work field has currently been necessary for students studying in a specific subject field. Designing an English course for EFL students learning in a specific subject field requires a needs analysis. This research aims to investigate target needs of EFL students learning in economics field in order to be able to communicate both personally or professionally. The purpose of this research is also for developing an English syllabus for economics students based on the need… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 3 publications
1
3
0
Order By: Relevance
“…Thus, students expected to have more lessons on writing and speaking, particularly in writing a report and having a formal conversation. The results from Saefullah and Nugraha (2020) were in line with the previous research carried out by Saientisna (2019) in terms of students' lack of speaking skills. The researcher reported that students encountered difficulties in speaking and listening to materials in English.…”
Section: Introductionsupporting
confidence: 89%
See 3 more Smart Citations
“…Thus, students expected to have more lessons on writing and speaking, particularly in writing a report and having a formal conversation. The results from Saefullah and Nugraha (2020) were in line with the previous research carried out by Saientisna (2019) in terms of students' lack of speaking skills. The researcher reported that students encountered difficulties in speaking and listening to materials in English.…”
Section: Introductionsupporting
confidence: 89%
“…Thirty-one respondents (77.5%) stated that materials related to English instructions in the economy is an aspect that should be embedded in English courses. Ekayati et al (2020) and Saefullah and Nugraha (2020) addressed in their studies that understanding instruction or commands in economics became the most dominant want of students. Secondly, as university students, the learners will join a lot of international conferences or webinars whom the speakers use English.…”
Section: Target Situation Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The perspectives of graduates and students in visual communication design must be more in sync to fully understand the needs of English language learners (listening, speaking, reading, and writing). According to Saefullah & Nugraha (2020), the needs analysis results showed that English instruction should integrate four English abilities (speaking, listening, writing, and reading) to meet the students' demands. The author has investigated and identified the learners' information on English proficiency to identify their current English language skills and their strengths and weaknesses.…”
Section: Learners' English Proficiency Information Concerning Languag...mentioning
confidence: 99%